Pengaruh Keterampilan Rias terhadap Kepercayaan Diri dalam Mempromosikan Jasa Makeup di Media Sosial - Devy Ayu Angraini; Febri Silvia; Rahmiati; Mimi Yupelmi (Lembaga Yasin AlSys, 2026)
Students in the Cosmetology and Beauty Study Program receive practical makeup training, including traditional West Sumatran bridal makeup, which is presumed to be associated with their confidence in promoting makeup services through social media. This study aimed to analyze the contribution of traditional West Sumatran bridal makeup skills to students’ confidence in promoting makeup services on social media. The study employed a quantitative approach with an ex post facto design. The sample comprised all 80 students from the 2022 cohort, selected using total sampling. Data were collected using a Likert-scale questionnaire and documentation of practical makeup scores. The research instrument was declared valid based on the calculated r-values, which exceeded the critical r-value of 0.361, and reliable, with a Cronbach’s alpha value of 0.928. The descriptive analysis showed that the students’ makeup skills were in the very good category, with a respondent achievement level of 89.62%, while their self-confidence was also in the very good category, with a respondent achievement level of 90.24%. Because the normality test indicated that the data were not normally distributed (p < 0.05), the hypothesis was tested using the nonparametric Spearman’s rho correlation. The results showed a positive, very strong, and significant relationship between makeup skills and students’ self-confidence (ρ = 0.923; p < 0.001); therefore, H0 was rejected and H1 was accepted. The coefficient of determination was 85.2%, while the remaining 14.8% was associated with other variables, such as self-concept, self-esteem, experience, and educational background. These findings confirm that mastery of makeup skills is closely associated with students’ confidence in promoting makeup services on social media and reinforce Bandura’s self-efficacy theory regarding mastery experience as the primary source of self-belief.